Investigating the Risk Factors for Non Typhoidal Salmonella in Pediatric Populations: A Systematic Review - Widiyanto, Aris; Halimah, Trisakti; Mubarok, Ahmad Syauqi; Anasulfalah, Hakim; Atmojo, Joko Tri; Hanif, Ihsan (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The risk factors for non-typhoidal Salmonella infections in pediatric populations are not fully understood, but this remains a critical area of study for improving child health. The aim of this review is to systematically analyze the available literature about the risk factors of non typhoidal salmonella among pediatric populations. The risk factors for non-typhoidal Salmonella infections in children were examined in all papers published between 2019 and 2024 using a systematic review of the literature using PRISMA criteria. Google Scholar, PubMed, and ProQuest are the three electronic databases that the writers searched. The query "children” AND “risk factors” AND “non-typhoidal salmonella” OR “salmonellosis" was used. The outcomes were then examined appropriately. We initially identified 1983 articles and subsequently selected 7 articles that met the inclusion criteria. We identified several risk factors associated with non-typhoidal Salmonella infections and categorized them into four domains: environmental factors (such as open field waste disposal), behavioral habits (like inadequate handwashing), health conditions, and socio-demographic characteristics (such as lower parental education). Our review identified risk factors for non-typhoidal Salmonella infections in four domains: environmental factors, behavioral habits, health conditions, and socio-demographic characteristics.